2019
DOI: 10.18280/ria.330503
|View full text |Cite
|
Sign up to set email alerts
|

An Automobile Noise Prediction Model Based on Extension Data Mining Algorithm

Abstract: In recent years, the prediction of automobile noise has attracted much attention from the academia. This paper aims to develop an automobile noise prediction model based on basic vehicle parameters and vehicle speed, rather than the features calculated from noise data. First, the extension data mining (EDM) was adopted to preprocess the original data, select the features and establish the matter-element models of automobile noise. Then, the extremum entropy method (EEM), an improved information entropy method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Commercial software such as Altair DesignAI, and Knowledge base provide AI-powered product design and learning from design data in recent years [14,15]. Apart from machine learning models application in product design, several deep learning applications are discussed in the various articles [10,11], that showcased new possibilities in the product development cycle. In sections 3 and 4, the research methodology and data generation setup are discussed in detail.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Commercial software such as Altair DesignAI, and Knowledge base provide AI-powered product design and learning from design data in recent years [14,15]. Apart from machine learning models application in product design, several deep learning applications are discussed in the various articles [10,11], that showcased new possibilities in the product development cycle. In sections 3 and 4, the research methodology and data generation setup are discussed in detail.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They demonstrated that multitask ANN models are effective for extracting common characteristics from multiple tasks and modelling the noise and acoustic quality of an induction motor. Lu and Wang [15] developed an ANN prediction model for automobile interior noise based on an extension data mining (EDM) algorithm considering basic vehicle parameters, such as the total number of engine valves, engine torque, vehicle, and vehicle speed as inputs of the model. Çelebi et al [16] used an ANN to predict the sound and vibration of a diesel engine.…”
Section: Introductionmentioning
confidence: 99%